PENGARUH FASILITAS KERJA, LINGKUNGAN KERJA DAN KOMPENSASI TERHADAP KINERJA APARATUR DESA PADA KANTOR DESA PEKAN KAMIS KEC.TEMBILAHAN HULU - MULYANA; AGUS MAULANA (AMNESIA (JURNAL MANAJEMEN SUMBER DAYA MANUSIA), 2023)
The purpose of this study is to determine the effect of work facilities, work environment and compensation on the performance of village apparatus in Pekan Kamis, Tembilahan Hulu sub-district. The population of this study is all apparatu’s totaling 47 people. Researchers used population research using the census method. The results of the study show that the work facilities variable has a direct and significant positive effect on employee performance, the work environment variable has no direct and significant positive effect on employee performance and the compensation variable has no direct and significant positive effect on employee performance, there is a significant influence from the independent variables (work facilities, work environment and compensation) on the dependent variable (performance). Based on the results of the F test there is a significant effect of the independent variables (work facilities, work environment and compensation) on the dependent variable (performance). The value of the coefficient of determination is obtained by a number of 0,351 so that it can be concluded that the variables of work facilities, work environment and compensation contribute to the employee variable performance by 35,1%. While the remaining 64,1% is influenced by other factors outside the independent variables in this study.